Penerapan Karate dalam Sikap Disipilin dan Bertanggung Jawab Anak Sekolah Dasar - Zulfika, Siti; Zumrotun, Erna (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to explore the application of karate martial arts to the development of discipline and responsibility in elementary school children. Using qualitative research methods, the study involved participant observation, in-depth interviews with teachers, karate coaches, and parents, and analysis of documentation related to the application of karate. The results showed that participation in regular karate training contributed positively to the improvement of students' discipline and sense of responsibility. The discipline taught through training in karate helps children understand the importance of rules and consistency. In addition, the responsibility instilled through the cultivation of attitudes demonstrated in karate training strengthens their ability to take responsibility for their own actions. The implications of these findings suggest that karate can be an effective tool in the character education of primary school children, with the potential to enhance life skills that are important for their future development.